2005
DOI: 10.1111/j.1476-8070.2005.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

Drawings of Emotionally Characterised Figures by Children from Different Educational Backgrounds

Abstract: Previous research has shown that children systematically alter the size and colour of their drawings in response to the emotional character of the figures which they draw. However, these findings have been demonstrated only with children receiving mainstream Western education. This experiment was designed to investigate whether children receiving a different kind of education also use scaling and colour differentially for depicting figures of contrasting emotional significance. 76 children, 44 children from ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 13 publications
(7 reference statements)
2
15
0
Order By: Relevance
“…However, the majority of claims to the effect that colour choice is emotionally significant in children's drawings have been based on professional observation rather than on formal experimentation (Hammer, 1997;Malchiodi, 1998;McNiff, 1992). Yet, recent experimental research has addressed previous methodological concerns (see Burkitt et al, 2003bBurkitt et al, , 2004Burkitt et al, , 2005 and shown that children systematically alter their choice of specific colours depending on the emotional descriptions of the figures and the way they felt about specific colours.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the majority of claims to the effect that colour choice is emotionally significant in children's drawings have been based on professional observation rather than on formal experimentation (Hammer, 1997;Malchiodi, 1998;McNiff, 1992). Yet, recent experimental research has addressed previous methodological concerns (see Burkitt et al, 2003bBurkitt et al, , 2004Burkitt et al, , 2005 and shown that children systematically alter their choice of specific colours depending on the emotional descriptions of the figures and the way they felt about specific colours.…”
Section: Introductionmentioning
confidence: 99%
“…Recent systematic research has only sampled children from across England (e.g. Burkitt et al, 2003bBurkitt et al, , 2004Burkitt et al, , 2005 and has not included a direct comparison between two cultural groups in one study.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the base of having resort to painting in professional media lies the opinion of "Emotional and communicative components are included in the drawing". Several studies have been conducted in order to prove that child's personality and state of mind at that moment can be understood on the basis of child's drawings and that subject's drawings of which are made by child may express several meanings for children (Burkitt, Barret and Davis, 2005).…”
Section: Child and Paintingmentioning
confidence: 99%